Optimizing the Role of Women Through the Entrepreneurship Education Program at PKBM Arrahman, Talabiu Village, Bima Regency - hendra, hendra; Asmiatiningsih, Sri; Junaidin, Junaidin; Taufiq, Muhammad; Arman, Arman; Rijal, uhammad Nur; Lutfi, Muhamad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Entrepreneurial Skills Education is an important program to improve entrepreneurial skills and knowledge, especially in the face of increasingly fierce economic competition. This program is designed to provide knowledge and skills and form an entrepreneurial attitude in participants, with the main goal of creating new business opportunities and improving community welfare. One of the PKW implementations was carried out at PKBM Arrahman in Talabiu Village, Woha District, Bima Regency, which focused on sewing skills training. This training aims to empower women by providing practical skills in sewing, which can be used to open an independent business or increase job opportunities. The training activities, which take place from August to October 2024, involve various learning methods including lectures, socialization, and practical training. With an approach that includes business opportunity identification, entrepreneurial learning, and business mentoring, this training equips participants with technical knowledge of design, material selection, cutting techniques, and fashion finishing. The results of the training showed an improvement in the sewing skills of the participants, which can now produce better quality products and reduce dependence on outside services. This training also has a significant impact in reducing unemployment in Talabiu Village, increasing community enthusiasm for entrepreneurship, and encouraging the opening of new businesses. However, for long-term success, it is important for participants to be more disciplined in financial records and pay attention to managerial aspects. Overall, this training not only improves technical skills but also has a positive economic impact on society, with the potential to operate optimally and sustainably in the future.